Detection and characterization of soluble proteins of sheep pox virus - MALIK, Y P S; CHAND, P (The Indian Journal of Animal Sciences, 2010)
Soluble proteins of sheep pox virus produced in lamb testis (LT) cells were investigated using graded precipitation of the virus-free culture supernatants with saturated ammonium sulphate solution. The proteins were separated from infected culture supernatants at 45% (A), between 45 and 60% (B) and from 60 to 80% (C) saturation of ammonium sulphate. SDS-PAGE and immunoblot analyses of the soluble proteins revealed a total of 33 and 24 proteins, respectively, with molecular weights ranging from 14 to 181 kDa. Of the 33 soluble proteins, 15 proteins in preparation A, 30 in B and 28 in C were detected in SDS-PAGE, whereas 6 proteins in preparation A, 21 in B and 18 in C showed reaction in immunoblotting. In SDS-PAGE of partially purified virus preparation (PPV) 18 proteins were detected. Of these, 8 were common with the proteins present in soluble protein preparations (A/B/C). These soluble proteins could be used as diagnostic antigen.